2006
DOI: 10.1080/01446190600953805
|View full text |Cite
|
Sign up to set email alerts
|

Approximately predicting the cost and duration of school reconstruction projects in Taiwan

Abstract: Regression and neural network models have been developed to predict the cost and duration of projects for the reconstruction of schools which must be quickly rebuilt. Data for the school reconstruction projects in central Taiwan, which received the most serious damage from the Chi-Chi Earthquake, were collected and analysed. The analytical results demonstrate that the floor area provides a good basis for estimating the cost and duration of school reconstruction projects, and suggest that the neural network mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Kaka and Price (1991), in the UK, and Chan and Kumaraswamy (1995) and Chan (1999), in Hong Kong, investigated the application of BTC model. Elsewhere in the world, Chen and Huang (2006) studied in the model in Taiwan, Chan (2001) and Endut et al (2006) examined it in Malaysia, Ogunsemi and Jagboro (2006) developed the model in Nigeria, and Hoffman et al (2007) re-examined the relationship in the USA. Moreover, Le-Hoai et al (2009) tried to fit empirical building project data for the BTC model in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaka and Price (1991), in the UK, and Chan and Kumaraswamy (1995) and Chan (1999), in Hong Kong, investigated the application of BTC model. Elsewhere in the world, Chen and Huang (2006) studied in the model in Taiwan, Chan (2001) and Endut et al (2006) examined it in Malaysia, Ogunsemi and Jagboro (2006) developed the model in Nigeria, and Hoffman et al (2007) re-examined the relationship in the USA. Moreover, Le-Hoai et al (2009) tried to fit empirical building project data for the BTC model in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Chan [9] introduced an appropriate BTC model on the Malaysian construction industry through conducting a similar study for public projects between the late 1980s and the early 1990s. Furthermore, Chen and Huang [11] showed that the original BTC model is suitable only for private sector's projects. Moreover, Le-Hoai and Lee [22] indicated that the time-cost relationship can be implemented in the building projects in South Korea.…”
Section: Model Validationmentioning
confidence: 99%
“…Hoffman et al [16] re-examined BTC model in the USA, Ogunsemi and Jagboro [25] developed time-cost model in Nigeria. Chen and Huang [11] investigated the time-cost model in Taiwan, Endut et al [14] and Chan [9] carried out the model in Malaysia. Bromilow and Henderson [5], Bromilow et al [6,7], Sidwell [28], Walker [31], Ng et al [24], and Love et al [23] have standardized BTC model in Australia.…”
Section: A Relationship Between Time and Costmentioning
confidence: 99%
“…Chen and Huang [11] analyze retroft costs and duration for schools in Taiwan. The authors also compare linear regression to neural networks.…”
Section: Existing Literature and Alternative Methodologiesmentioning
confidence: 99%
“…On the surface, the procedure bears some similarity to standard re-sampling techniques such as the bootstrap, except that it is applied before the analysis. 11 11 The procedure is referred to as a generic "Monte Carlo Simulation" in FEMA 156/157 [4,5].…”
Section: The Fema 156/157 "Super Database"mentioning
confidence: 99%